Ministry Of Trade And Industry Decree No. 1221 Of The Year 2017 Amending Certain Provisions of The statute of rules implementing the provisions of Law No. 118 of the year 1975 on import and export = وزارة التجارة والصناعة قرار رقم 1221 لسنة 2017 بتعديل بعض أحكام لائحة القواعد المنفذة لأحكام القانون رقم 118 لسنة 1975 فى شأن الاستيراد والتصدير - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic